Preparation method of high-conductivity lithium manganese iron phosphate material

By using stereo sheet niobium pentoxide as a conductive frame and combining carbon coating technology, the poor conductivity of lithium manganese iron phosphate material is solved, and its performance in lithium-ion batteries is significantly improved.

CN119490226APending Publication Date: 2025-02-21HUBEI THREE GORGES LAB
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411493651.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The conductivity of lithium manganese iron phosphate material is extremely poor, resulting in limited commercial application in lithium-ion batteries.

Method used

By defining a three-dimensional sheet niobium pentoxide as a conductive frame structure, lithium manganese iron phosphate is filled and coated on the outside of the conductive frame, and the strong coordination effect of the Nb-O bond in Nb2O5 accelerates ion diffusion and electron transport, and inhibits Mn3+ Jahn-Teller effect. At the same time, the carbon layer is coated to further improve the conductivity.

Benefits of technology

The conductive performance of spherical lithium manganese phosphate material is significantly improved, and the discharge capacity and rate performance of the buckle battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490226A_ABST
    Figure CN119490226A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-conductivity lithium manganese iron phosphate material, the preparation raw materials of the lithium manganese iron phosphate material comprise a three-dimensional sheet niobium pentoxide conductive frame, a manganese source, an iron source, a lithium source and a carbon source, the niobium pentoxide conductive frame is of a sheet porous structure, the structure can accommodate the lithium manganese iron phosphate material to be filled between sheet layers and pores, so as to form a three-dimensional spherical structure; the obtained spherical lithium manganese iron phosphate material has excellent conductivity and processability, and can show relatively high discharge capacity of a button cell when being used as a positive electrode material of a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-conductivity lithium manganese iron phosphate material and a preparation method and application thereof. Background Art

[0002] At present, the most widely used cathode active materials for lithium-ion batteries include lithium cobalt oxide, lithium manganese oxide, ternary materials, and lithium iron phosphate. Among them, lithium iron phosphate has attracted widespread attention due to its high theoretical capacity, good cycle performance, excellent safety performance, wide source of raw materials, low cost, and environmental friendliness. However, lithium iron phosphate batteries have the disadvantage of low voltage, and their electrode voltage is 3.2 V. Lithium iron manganese phosphate and lithium iron phosphate are both phosphate-based cathode active materials for lithium-ion batteries, and their theoretical capacity is 170 mAh / g. Compared with lithium iron phosphate, lithium iron manganese phosphate has a higher voltage, and its electrode voltage is 4.1 V, which is higher than 3.2 V of lithium iron phosphate. It has certain advantages in specific energy and specific power. Therefore, the development of lithium iron manganese phosphate with excellent electrochemical performance as a cathode material for lithium-ion batteries has a very broad market prospect.

[0003] However, the conductivity of lithium manganese iron phosphate is extremely poor. According to the first principles, the electron energy of electron transition in lithium iron phosphate is 0.3 eV, which is a semiconductor material, while the electron energy of electron transition in lithium manganese iron phosphate is 2 eV, which is an insulating material. This makes it very difficult to prepare lithium manganese iron phosphate materials that can be reversibly charged and discharged, which limits the commercial application of lithium manganese iron phosphate.

[0004] At present, in order to improve the electrochemical performance of LMFP materials, the main modification methods are nano-sizing, carbon coating and metal ion doping. Nano-sizing is mainly achieved by extending the sanding time, which increases the difficulty of processing; carbon coating increases the specific surface area of ​​lithium manganese iron phosphate, making it unevenly dispersed during processing; metal ion doping is not conducive to structural stability, and the doping amount should not be too high. Based on the above experience, the present invention will focus on how to further improve the conductivity of lithium manganese iron phosphate, thereby improving its charge and discharge capacity. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a highly conductive spherical lithium manganese iron phosphate material, which is prepared by a solid phase method. By limiting the three-dimensional sheet-like niobium pentoxide to a conductive framework structure, lithium manganese iron phosphate is filled and coated on the outside of the conductive framework, and the strong coordination effect of the Nb-O bond in the core Nb2O5 can be used to accelerate the ion diffusion and electron transmission in the nanoparticles, inhibiting the Mn 3+The Jahn-Teller effect effectively improves the conductivity of the spherical lithium manganese iron phosphate material. The carbon layer coated on the outside of the spherical lithium manganese iron phosphate material further improves the conductivity of the spherical lithium manganese iron phosphate material, which will help to increase the discharge capacity of the button battery.

[0006] As a preferred technical solution of the present invention, the method for preparing the highly conductive lithium manganese iron phosphate material comprises the following steps: A method for preparing a three-dimensional sheet-like niobium pentoxide conductive frame, the preparation method comprising the following steps: (1) dissolving niobium oxalate in a mixed solution of ethylene glycol and water, adding nano-silicon dioxide and stirring thoroughly to obtain a milky white suspension; (2) adding a certain amount of alkaline solution to adjust the pH to neutral, and then performing the first hydrothermal treatment in a high-pressure reactor; (3) adding an alkaline solution to the above reactor to adjust the pH to alkaline, and performing a second hydrothermal treatment in the high-pressure reactor; (4) The obtained hydrothermal precipitation product is annealed in air to obtain the above-mentioned three-dimensional sheet structure.

[0007] In the mixed solution of ethylene glycol and water in step (1), the volume ratio of ethylene glycol to water is 3:5-10; Preferably, the particle size of the nano-silicon dioxide in step (1) is distributed in the range of 1 to 50 nm; the particle size of the nano-silicon dioxide is distributed in the range of 1 to 50 nm, and the molar ratio of niobium oxalate to nano-silicon dioxide is 5-20:1.

[0008] Preferably, the alkaline solution in step (2) is selected from any one of aqueous ammonia, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, and potassium carbonate solution; The neutral pH refers to adjusting the pH to 6.5-7.5; The first hydrothermal reaction temperature is 100-150°C; the reaction time is 24-30h.

[0009] Preferably, the alkaline solution in step (3) is selected from any one of aqueous ammonia, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, and potassium carbonate solution; The neutral pH means that the pH is adjusted to 8.5-12.5; The first hydrothermal reaction temperature is 200-300°C; the reaction time is 12-20h.

[0010] Preferably, the annealing treatment temperature in step (4) is 500-800°C, and the heating rate is 3-5°C / min; Preferably, the annealing treatment time in step (4) is 4 to 6 hours.

[0011] Another object of the present invention is to provide a method for preparing the lithium manganese iron phosphate, the method comprising the following steps: (1) mixing a manganese source, an iron source, a lithium source, a phosphorus source, and a carbon source, and then adding water and sand grinding the mixture to a certain particle size; (2) After the sand grinding is completed, the prepared niobium pentoxide conductive frame is added and dispersed evenly at a low speed; (3) spray granulating the slurry dispersed in step (2); (4) The spray granulated powder is placed in an inert atmosphere for sintering to obtain a lithium manganese iron phosphate positive electrode material.

[0012] The lithium source includes lithium carbonate or lithium hydroxide; The manganese source includes one of manganese carbonate, manganese acetate, manganese phosphate, manganous phosphate, manganese trioxide, and manganese tetraoxide; The iron source includes one of ferric nitrate, ferric oxide, ferric phosphate, ferrous acetate, and ferrosoferric oxide; The phosphorus source includes one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, iron phosphate, manganese phosphate, and manganous phosphate; The carbon source includes one or more of citric acid, sucrose, glucose, carbon nanotubes, and polyethylene glycol.

[0013] In the technical solution of the present invention, step (1) also includes a doping element, wherein the doping element includes at least one of Ti, V, Co, Ni, Nb, Mg and the like, and the dopant is a corresponding oxide, ammonium salt or oxalate, and the content of the doping element is 0.01% to 5%.

[0014] In the step (1), a manganese source, an iron source, a lithium source, a phosphorus source, a carbon source, and a selectively added dopant are added to pure water for ball milling; the slurry after ball milling is transferred to a sand mill for grinding, and the sand milling particle size is controlled to be within a certain range; the particle size D50 of the slurry after sand milling is controlled to be ≤300 nm, and the speed of the sand mill is controlled within 1000 rpm.

[0015] Preferably, the inlet air temperature of the spray is 160-240°C, and the outlet air temperature of the spray is 75-85°C.

[0016] Preferably, high temperature sintering is performed under nitrogen protection, the sintering temperature is 600-800° C., and the holding time is 6-12 h.

[0017] Preferably, after sintering to obtain the lithium manganese iron phosphate black material, it is screened, and the screening screen is not larger than 325 meshes.

[0018] The particle size of the spherical lithium manganese iron phosphate material is 2 to 6 μm; Preferably, the mass percentage of the niobium pentoxide conductive framework in the spherical lithium manganese iron phosphate material is 1-3%; this added amount is the added amount of the niobium pentoxide conductive framework in the raw material.

[0019] Preferably, the mass percentage of carbon coating in the spherical manganese ferrophosphate precursor is 1-3%.

[0020] Based on the above preparation method, the present invention provides a spherical lithium manganese iron phosphate material, which includes a three-dimensional sheet-like niobium pentoxide conductive frame and a lithium manganese iron phosphate material.

[0021] The three-dimensional sheet-like niobium pentoxide conductive frame is a sheet-like structure, which can accommodate the lithium iron manganese phosphate material to be filled between its sheets to form a three-dimensional spherical structure. Thanks to the good electronic conductivity of niobium pentoxide, the sheet structure can provide a conductive channel from the inside to the outside, thereby serving as a conductive frame to improve the conductivity of the lithium iron manganese phosphate material.

[0022] Compared with the prior art, the present invention has the following beneficial effects: By limiting the three-dimensional sheet-like niobium pentoxide to a conductive framework structure, and filling and coating the lithium manganese iron phosphate on the outside of the conductive framework, the strong coordination effect of the Nb-O bond in the core Nb2O5 can be used to accelerate the ion diffusion and electron transmission in the nanoparticles, thereby inhibiting the Mn 3+ The Jahn-Teller effect effectively improves the conductivity of the spherical lithium manganese iron phosphate material. The carbon layer coated on the outside of the spherical lithium manganese iron phosphate material further improves the conductivity of the spherical lithium manganese iron phosphate material, which will help to improve the discharge capacity and rate performance of the button battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings of the present invention are provided only for illustrative purposes, so as to enable those skilled in the art to understand and implement the present invention after reading the present invention, rather than to limit the protection scope of the present invention.

[0024] Figure 1 This is a SEM image of the three-dimensional sheet-like niobium pentoxide structure prepared in Example 1 of the present invention.

[0025] Figure 2 This is a SEM image of the three-dimensional sheet-like niobium pentoxide structure prepared in Comparative Example 3 of the present invention.

[0026] Figure 3 This is a SEM image of lithium manganese iron phosphate prepared in Example 3 of the present invention.

[0027] Figure 4 It is a comparison chart of 0.1C charge and discharge curves of lithium manganese iron phosphate button batteries prepared in Example 3 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0029] Example 1 A method for preparing highly conductive lithium manganese iron phosphate comprises the following steps: Dissolve 5.38g of niobium oxalate in a mixed solution of ethylene glycol (30mL) and water (50mL), add 0.06g of nano-silicon dioxide, stir evenly to obtain a milky suspension, then gradually add a 0.1mol / L sodium hydroxide solution until the pH shows 7.2. Transfer the solution to a high-pressure reactor and keep it at 150°C for 24h. After the hydrothermal treatment is completed, continue to add a 0.1mol / L sodium hydroxide solution, adjust the pH to 11.0, keep it at 200°C for 12h, and then anneal the precipitate at 500°C in a muffle furnace for 5h to obtain a three-dimensional sheet-like niobium pentoxide structure.

[0030] Add 500 g of pure water to the ball mill, weigh 91.4 g of ammonium dihydrogen phosphate, and then slowly add 49.0 g of lithium carbonate. The reaction of ammonium dihydrogen phosphate and lithium carbonate will produce a large number of bubbles. After the reaction is complete and no bubbles are generated, add 80.0 g of anhydrous ferric phosphate, 60.7 g of manganese tetraoxide, 5.7 g of glucose, 3.8 g of polyethylene glycol, and 0.53 g of titanium dioxide. Ball milling for 1 h to fully mix the above-mentioned raw materials such as iron source, lithium source, manganese source, phosphorus source, carbon source, and metal ion dopant, and then transfer to sand milling. After sand milling at a speed of 2500 rpm for 30 min, the D50 of slurry 2 is measured by a particle size analyzer to be 295 nm. Add 2.82 g of the above-mentioned niobium pentoxide powder, sand mill at a speed of 500 rpm for 5 min, and then granulate by spray drying to obtain a brown precursor powder. The precursor was placed in a graphite crucible and sintered at high temperature under nitrogen atmosphere at 650°C for 10 hours and then cooled naturally. The lithium manganese iron phosphate cathode material was then obtained after sieving and removing iron.

[0031] Example 2 A method for preparing highly conductive lithium manganese iron phosphate comprises the following steps: Dissolve 5.38g of niobium oxalate in a mixed solution of ethylene glycol (30mL) and water (50mL), add 0.06g of nano-silicon dioxide, stir evenly to obtain a milky suspension, then gradually add a 0.1mol / L sodium hydroxide solution until the pH shows 6.8. Transfer the solution to a high-pressure reactor and keep it at 150°C for 24h. After the hydrothermal treatment is completed, continue to add a 0.1mol / L sodium hydroxide solution, adjust the pH to 11.5, keep it at 200°C for 12h, and then anneal the precipitate at 800°C in a muffle furnace for 5h to obtain a three-dimensional sheet-like niobium pentoxide structure.

[0032] Add 500 g of pure water to the ball mill, weigh 91.4 g of ammonium dihydrogen phosphate, and then slowly add 49.0 g of lithium carbonate. The reaction of ammonium dihydrogen phosphate and lithium carbonate will produce a large number of bubbles. After the reaction is complete and no bubbles are generated, add 80.0 g of anhydrous ferric phosphate, 60.7 g of manganese tetraoxide, 5.7 g of glucose, 3.8 g of polyethylene glycol, and 0.53 g of titanium dioxide. Ball milling for 1 h to fully mix the above-mentioned raw materials such as iron source, lithium source, manganese source, phosphorus source, carbon source, and metal ion dopant, and then transfer to sand milling. After sand milling at a speed of 2500 rpm for 30 min, the slurry D50 is measured by a particle size analyzer to be 295 nm, and 2.82 g of the above-mentioned niobium pentoxide powder is added. Sand milling at a speed of 500 rpm for 5 min, and then granulation by spray drying to obtain a brown precursor powder. The precursor was placed in a graphite crucible and sintered at high temperature under nitrogen atmosphere at 650°C for 10 hours and then cooled naturally. The lithium manganese iron phosphate cathode material was then obtained after sieving and removing iron.

[0033] Example 3 A method for preparing highly conductive lithium manganese iron phosphate comprises the following steps: Dissolve 5.38g of niobium oxalate in a mixed solution of ethylene glycol (30mL) and water (50mL), add 0.06g of nano-silicon dioxide, stir evenly to obtain a milky suspension, then gradually add a 0.1mol / L sodium hydroxide solution until the pH shows 6.7. Transfer the solution to a high-pressure reactor and keep it at 150°C for 24h. After the hydrothermal treatment is completed, continue to add a 0.1mol / L sodium hydroxide solution, adjust the pH to 12.4, keep it at 200°C for 12h, and then anneal the precipitate at 800°C in a muffle furnace for 5h to obtain a three-dimensional sheet-like niobium pentoxide structure.

[0034] First, add 500 g of pure water to the ball mill, weigh 82.7 g of lithium dihydrogen phosphate, and then slowly add 19.6 g of lithium carbonate. The reaction of lithium dihydrogen phosphate and lithium carbonate will produce a large number of bubbles. After the reaction is complete and no bubbles are generated, add 80.0 g of anhydrous ferric phosphate, 60.7 g of manganese tetraoxide, 5.7 g of glucose, 3.8 g of polyethylene glycol, and 0.53 g of titanium dioxide. Ball milling for 1 h to fully mix the raw materials such as iron source, lithium source, manganese source, phosphorus source, carbon source, and metal ion dopant, and then transfer to sand milling. After sand milling at a speed of 2500 rpm for 30 min, the slurry D50 is measured by a particle size analyzer to be 295 nm. Add 2.82 g of the above-mentioned niobium pentoxide powder, sand mill at a speed of 500 rpm for 5 min, and then granulate by spray drying to obtain a brown precursor powder. The precursor was placed in a graphite crucible and sintered at high temperature under nitrogen atmosphere at 650°C for 10 hours and then cooled naturally. The lithium manganese iron phosphate cathode material was then obtained after sieving and removing iron.

[0035] Example 4 A method for preparing highly conductive lithium manganese iron phosphate comprises the following steps: Dissolve 5.38g of niobium oxalate in a mixed solution of ethylene glycol (30mL) and water (50mL), add 0.06g of nano-silicon dioxide, stir evenly to obtain a milky suspension, then gradually add a 0.1mol / L sodium hydroxide solution until the pH shows 7.3. Transfer the solution to a high-pressure reactor and keep it at 150°C for 24h. After the hydrothermal treatment is completed, continue to add a 0.1mol / L sodium hydroxide solution, adjust the pH to 10.5, keep it at 200°C for 12h, and then anneal the precipitate at 800°C in a muffle furnace for 5h to obtain a three-dimensional sheet-like niobium pentoxide structure.

[0036] First, add 500 g of pure water to the ball mill, weigh 82.7 g of lithium dihydrogen phosphate, and then slowly add 19.6 g of lithium carbonate. The reaction of lithium dihydrogen phosphate and lithium carbonate will produce a large number of bubbles. After the reaction is complete and no bubbles are generated, add 80.0 g of anhydrous ferric phosphate, 60.7 g of manganese tetraoxide, 5.7 g of glucose, 3.8 g of polyethylene glycol, and 0.53 g of titanium dioxide. Ball mill for 1 h to fully mix the raw materials such as iron source, lithium source, manganese source, phosphorus source, carbon source, and metal ion dopant. Then transfer to sand milling. After sand milling at a speed of 2500 rpm for 1 h, the slurry D50 is measured by a particle size analyzer to be 245 nm. Add 2.82 g of the above-mentioned niobium pentoxide powder, sand mill at a speed of 500 rpm for 5 min, and then granulate by spray drying to obtain a brown precursor powder. The precursor was placed in a graphite crucible and sintered at high temperature under nitrogen atmosphere at 650°C for 10 hours and then cooled naturally. The lithium manganese iron phosphate cathode material was then obtained after sieving and removing iron.

[0037] Example 5 A method for preparing highly conductive lithium manganese iron phosphate comprises the following steps: Dissolve 5.38g of niobium oxalate in a mixed solution of ethylene glycol (30mL) and water (50mL), add 0.06g of nano-silicon dioxide, stir evenly to obtain a milky suspension, then gradually add a 0.1mol / L sodium hydroxide solution until the pH shows 6.8. Transfer the solution to a high-pressure reactor and keep it at 150°C for 24h. After the hydrothermal treatment is completed, continue to add a 0.1mol / L sodium hydroxide solution to adjust the pH to 10.2, keep it at 200°C for 12h, and then anneal the precipitate at 800°C in a muffle furnace for 5h to obtain a three-dimensional sheet-like niobium pentoxide structure.

[0038] First, add 500 g of pure water to the ball mill, weigh 82.7 g of lithium dihydrogen phosphate, and then slowly add 19.6 g of lithium carbonate. The reaction of lithium dihydrogen phosphate and lithium carbonate will produce a large number of bubbles. After the reaction is complete and no bubbles are generated, add 80.0 g of anhydrous ferric phosphate, 60.7 g of manganese tetraoxide, 8.6 g of glucose, 5.7 g of polyethylene glycol, and 0.53 g of titanium dioxide. Ball milling for 1 h to fully mix the raw materials such as iron source, lithium source, manganese source, phosphorus source, carbon source, and metal ion dopant, and then transfer to sand milling. After sand milling at a speed of 2500 rpm for 30 min, the slurry D50 is measured by a particle size analyzer to be 295 nm. Add 2.82 g of the above-mentioned niobium pentoxide powder, sand mill at a speed of 500 rpm for 5 min, and then granulate by spray drying to obtain a brown precursor powder. The precursor was placed in a graphite crucible and sintered at high temperature under nitrogen atmosphere at 650°C for 10 hours and then cooled naturally. The lithium manganese iron phosphate cathode material was then obtained after sieving and removing iron.

[0039] Comparative Example 1 A method for preparing lithium manganese iron phosphate, which differs from Example 1 in that the above-mentioned three-dimensional sheet-like niobium pentoxide structure is not added in this experiment.

[0040] Comparative Example 2 A method for preparing lithium manganese iron phosphate, which differs from Example 3 in that the above-mentioned three-dimensional sheet-like niobium pentoxide structure is not added in this experiment.

[0041] Comparative Example 3 A method for preparing lithium manganese iron phosphate, which differs from Example 3 in that only one hydrothermal reaction is performed, that is, the hydrothermal reaction is performed only under the condition of pH 6.7, and then the hydrothermal reaction product is annealed at 800° C. for 5 h.

[0042] Furthermore, in order to verify the progress of the embodiments of the present application, the above embodiments and comparative examples were tested as follows: 1. The morphology of the niobium pentoxide structures prepared in Example 3 and Comparative Example 3 was observed using a scanning electron microscope. The SEM image of the niobium pentoxide structure annealed at 800°C for 5 hours in Example 3 is shown in the attached figure. Figure 1 As shown in the figure, the structure is three-dimensional, the layers are clear, and the outer contour is spherical; the SEM image of the niobium pentoxide structure in Comparative Example 3, which was subjected to only one hydrothermal reaction, is shown in the attached figure. Figure 2 As shown, the structure is three-dimensional and the outer contour is basically spherical, but the layer state is discontinuous, the structure is incomplete, and a stable conductive channel cannot be formed.

[0043] 2. The morphology of the highly conductive lithium manganese iron phosphate prepared in Example 3 was observed using a scanning electron microscope, as shown in the attached figure. Figure 3 As shown, the primary particles are filled evenly to form a rounded three-dimensional spherical structure.

[0044] 3. The positive electrode material powders prepared in the above-mentioned embodiments and comparative examples were tested for powder resistance, specific surface area and carbon content.

[0045] 4. The positive electrode materials prepared in the above embodiments and comparative examples were respectively made into button-type lithium-ion batteries, and the electrochemical properties of the materials were tested. The specific preparation steps are as follows: (1) Preparation of slurry: 23.3 g of the positive electrode material prepared in the above examples and comparative examples, 0.12 g of superconducting carbon black (SP) and 0.48 g of a binder polyvinylidene fluoride (PVDF) were added to a 500 mL agate ball mill, and 16 mg of solvent N-methylpyrrolidone (NMP) was added. The mixture was ball milled at a speed of 360 rpm for 4 h to prepare a slurry; (2) Slurry coating: adjust the scale of the scraper of the coating machine, evenly coat the milled slurry on the aluminum foil, and place the coated electrode in a vacuum drying oven at 120°C for 2 hours; (3) Rolling and punching: Place the aluminum foil coated with the slurry flatly in the middle of the roller and roll the electrode; place the front of the rolled electrode close to the punched hole and punch the electrode in sequence; the electrode diameter is 14 mm and the thickness is 0.05-0.10 mm; place the punched electrode in a vacuum drying oven at 120°C and bake for 2 hours; (4) Assembling button cells: In a glove box, assemble the negative electrode shell, spring sheet, steel sheet, lithium sheet, separator, positive electrode sheet and positive electrode shell in the order of 80 μL of electrolyte. Then, use a sealing machine to seal the button cell. The assembled button cell is used for subsequent electrochemical performance testing.

[0046] The 0.1C charge and discharge curves of the button cells corresponding to Example 3 and Comparative Example 2 are shown in the attached figure. Figure 4 As shown, after adding the above-mentioned three-dimensional flake niobium pentoxide structure, the conductivity of the material is significantly enhanced, the capacity is increased, and the polarization is reduced.

[0047] The test results of the above examples and comparative examples are shown in Table 1. After adding the three-dimensional sheet-like niobium pentoxide structure, the powder resistivity is significantly reduced, which proves the improvement of the conductivity of the positive electrode material. Reducing the sand milling end particle size and increasing the carbon coating amount will improve the conductivity to a certain extent, but the specific surface area will increase significantly, which is not conducive to the subsequent processing performance. Comprehensive comparison shows that the solution of Example 3 can significantly improve the conductivity while stabilizing the important indicator of specific surface area. The 0.1C charge and discharge curves of the button batteries corresponding to Example 3 and Comparative Example 2 are shown in the attached figure. Figure 4As shown, after adding the above-mentioned three-dimensional flake niobium pentoxide structure, not only the conductivity of the material is significantly enhanced, the capacity is increased, but the polarization is also significantly reduced.

[0048] Table 1 Test results .

Claims

1. A method for preparing a three-dimensional sheet-like niobium pentoxide conductive framework, characterized in that: The steps include: (1) dissolving niobium oxalate in a mixed solution of ethylene glycol and water, adding nano-silicon dioxide and stirring thoroughly to obtain a milky white suspension; (2) adding an alkaline solution to adjust the pH to neutral, followed by a first hydrothermal treatment in a high pressure reactor; (3) adding an alkaline solution to the above reactor to adjust the pH to alkaline, and performing a second hydrothermal treatment in the high-pressure reactor; (4) The obtained hydrothermal precipitation product is annealed in air to obtain the above-mentioned three-dimensional sheet structure.

2. The preparation method according to claim 1, characterized in that: In the mixed solution of ethylene glycol and water in step (1), the volume ratio of ethylene glycol to water is 3:5-10; The particle size of the nano silicon dioxide is distributed in the range of 1 to 50 nm, and the molar ratio of niobium oxalate to the nano silicon dioxide is 5-20:

1.

3. The preparation method according to claim 1, characterized in that: In step (2), the alkaline solution is selected from any one of aqueous ammonia, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, and potassium carbonate solution; The neutral pH refers to adjusting the pH to 6.5-7.5; The first hydrothermal reaction temperature is 100-150°C; the reaction time is 24-30h.

4. The preparation method according to claim 1, characterized in that: In step (3), the alkaline solution is selected from any one of aqueous ammonia, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, and potassium carbonate solution; The neutral pH means that the pH is adjusted to 8.5-12.5; The first hydrothermal reaction temperature is 200-300°C; the reaction time is 12-20h.

5. The preparation method according to claim 1, characterized in that: The annealing temperature in step (4) is between 500 and 800° C., and the annealing time is between 4 and 6 hours.

6. A three-dimensional sheet-like niobium pentoxide conductive frame, characterized in that: A three-dimensional sheet-like niobium pentoxide conductive frame prepared by the method described in any one of claims 1 to 5 has an outer contour that is roughly spherical and is an ultra-thin sheet-like structure with different growth directions at the center.

7. A method for preparing lithium manganese iron phosphate, characterized in that: The steps include: (1) mixing a manganese source, an iron source, a lithium source, a phosphorus source, and a carbon source, and then adding water and sand grinding the mixture to a certain particle size; (2) After sand grinding, add the niobium pentoxide conductive frame as described in claim 6 and disperse it evenly at a low speed; (3) spray granulating the slurry dispersed in step (2); (4) The spray granulated powder is placed in an inert atmosphere for sintering to obtain a lithium manganese iron phosphate positive electrode material.

8. The method for preparing lithium manganese iron phosphate according to claim 7, characterized in that: The lithium source includes lithium carbonate or lithium hydroxide; The manganese source includes one of manganese carbonate, manganese acetate, manganese phosphate, manganous phosphate, manganese trioxide, and manganese tetraoxide; The iron source includes one of ferric nitrate, ferric oxide, ferric phosphate, ferrous acetate, and ferrosoferric oxide; The phosphorus source includes one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, iron phosphate, manganese phosphate, and manganous phosphate; The carbon source includes one or more of citric acid, sucrose, glucose, carbon nanotubes, and polyethylene glycol. The particle size D50 of the slurry after sand grinding is controlled at ≤300 nm; The mass percentage of the niobium pentoxide conductive framework in step (2) is 1-3%.

9. The method for preparing lithium manganese iron phosphate according to claim 7, characterized in that: The temperature of the spray granulation in step (3) is 160-240°C; In step (4), high temperature sintering is carried out under nitrogen protection, the sintering temperature is 600-800°C, and the holding time is 6-12 h.

10. Lithium manganese iron phosphate prepared by the method according to any one of claims 7 to 9, characterized in that: The three-dimensional sheet-like niobium pentoxide conductive frame is a sheet-like structure, which accommodates the lithium iron manganese phosphate material and fills it between its sheets to form a three-dimensional spherical structure. The particle size of the spherical lithium iron manganese phosphate material is 2 to 6 μm.

Citation Information

Cited By

  • Particle size compounded and gradient carbon coated lithium manganese iron phosphate, preparation method thereof and positive electrode

    CN121282161A